Exploring peripheral fluid biomarkers for early detection of Alzheimer's disease in Down syndrome: A literature review - Charlotte Jacob; Marleen Tollenaere; Hanane Kachar; Marie-Claude Potier; Peter Paul De Deyn; Debby Van Dam (Heliyon)
People with Down Syndrome (DS) are at high risk of developing Alzheimer's disease dementia (AD) and cerebral amyloid angiopathy, which is a critical factor contributing to dementia in sporadic AD. Predicting and monitoring the decline and onset of dementia is a diagnostic challenge and of essence in daily care and support for people with DS. In this literature scoping review, we first summarize the different blood-based biomarkers for AD in DS. Next, we describe urine-based biomarkers for AD in DS and finally, we explore various blood-based biomarkers in the general AD population. Apart from the classic amyloid beta and Tau biomarkers, we also discuss more out-of-the-box biomarkers such as neurofilament light chain, Dual-specificity tyrosine-regulated kinase 1A, and monoaminergic biomarkers. These potential biomarkers could be a valuable addition to the established panel of fluid biomarkers.